Cytotoxic and toxicogenomic effects of silibinin in bladder cancer cells with different TP53 status - Oliveira, Daiane Teixeira de; Ventura Savio, Andre Luiz [UNESP]; Castro Marcondes, Joao Paulo de [UNESP]; Barros, Tatiane Martins; Barbosa, Ludmila Correia; Favero Salvadori, Daisy Maria [UNESP]; Silva, Glenda Nicioli da (Indian Acad Sciences, 2017)
Silibinin is a natural phenol found in the seeds of the milk thistle plant. Recent data have shown its effectiveness for preventing/treating bladder tumours. Therefore, in this study we investigated the cytotoxic and toxicogenetic activity of silibinin in bladder cancer cells with different TP53 statuses. Two bladder urothelial carcinoma cell lines were used: RT4 (wild-type TP53 gene) and T24 (mutated TP53 gene). Cell proliferation, clonogenic survival, apoptosis rates, genotoxicity and relative expression profile of FRAP/mTOR, FGFR3, AKT2 and DNMT1 genes and of miR100 and miR203 were evaluated. Silibinin promoted decreased proliferation and increased late apoptosis in TP53 mutated cells. Increased early apoptosis rates, primary DNA damage, and decrease of cell colonies in the clonogenic survival assay were detected in both RT4 and T24 cell lines. Down-regulation of FRAP/mTOR, AKT2, FGFR3, DNMT1 and miR100 expression occurred in RT4 cells. Modulation of miR203 was observed in both cell lines. In conclusion, despite the reduction of clone formation in both cell lines, the toxicogenomic effect of silibinin on FRAP/mTOR, AKT2, FGFR3, DNMT1 and miR100 was dependent on the TP53 status. Taken together, the data confirmed the role of silibinin as an antiproliferative compound, whose mechanism of action was related to the TP53 status.
Keywords: Bladder cancer; cell proliferation; genotoxicity; PI3K/AKT/FRAP-mTOR pathway; silibinin; TP53 gene